THE EFFECTIVENESS OF CINEMA THERAPY-BASED COGNITIVE BEHAVIOR THERAPY GROUP COUNSELING APPROACH TO REDUCE DECADENCE OF MORAL BEHAVIOR - Halimah, Cita Hermitha Noor; Purwati, Purwati; Lianasari, Lianasari (Prosiding University Research Colloquium, 2021)
This study aims to examine the effectiveness of group counseling with Cinema Therapy- Based Cognitive Behavior Therapy approach to reduce the decadence of adolescent moral behavior. This research is a pure experimental research using a model Pretest-Posttest Control Group Design.The subjects of this study were selected randomly. The samples taken in this study were 10 adolescents consisting of 5 adolescents as the experimental group and 5 adolescents as the control group. The data collection method was carried out using a decadence questionnaire of adolescent moral behavior. The data analysis method used in this study namely by using One way Anova Parametric Statistical analysis with the help of SPSS For Windows version 24. The results showed that the group counseling approach Cognitive Behavior Therapy Based on Cinema Therapyeffective in reducing the decadence of adolescent moral behavior. This is evidenced by the results of the One-way ANOVA Parametric Statistics test with a probability of sig. (2-tailed) 0.007 <0.05. Based on the results of the analysis and discussion, there is a difference in the average score of the decadence questionnaire on adolescent moral behavior between the experimental group and thethe average value (9.18%) which is higher than the control group with an average increase (5.59%). The results of the study can be concluded that group counselingCinema Therapy-Based Cognitive Behavior Therapy approach is effective in reducing the decadence of adolescent moral behavior.